Influence of Lactobacillus helveticus ZF22 and TR1-1-3 strains on the aromatic flavor of fermented sausages - Tian, Jianjun; Yang, Xueqian; Zhang, Kaiping; Zhao, Yanhong; Cheng, Feng; Jin, Ye (Frontiers in Nutrition, 2023)
In this study, five strains isolated from traditional Inner Mongolian air-dried meat products were used, two Lactobacillus helveticus strains, ZF22 and TR1-1-3, with potent antibacterial activity, acid, salt, and nitrite tolerance, were selected for this study. Lactic acid bacteria (LAB) (Lactobacillus helveticus ZF22 and TR1-1-3) were inoculated into fermented sausages at 107 CFU/g and their volatiles were studied during fermentation and storage. Clustering heat map and principal component analysis (PCA) were used to identify differentiating flavor components in uninoculated and inoculated sausages. The results showed that 72 volatile flavor substances were identified during the fermentation of the fermented sausages and that inoculation with Lactobacillus helveticus ZF22 and TR1-1-3 increased the proportion of acids, ketones and alkanes. Moreover, the clustering heat map demonstrated that esters such as ethyl isobutyrate, ethyl acetate, and ethyl valerate were more abundant in TR1-1-3 and ZF22 than ZR. The PCA analysis showed that the volatile compounds of the three fermented sausages were distributed in separate quadrants, suggesting that the volatile compound compositions of the three fermented sausages differed significantly. Our findings suggest that inoculating fermented sausages with Lactobacillus helveticus TR1-1-3 and ZF22 can improve flavor by enhancing the type and amount of flavor compounds.